Laryngeal Verrucous Carcinoma: A Systematic Review. (9th August 2016) - Echanique, Kristen A.; Desai, Stuti V.; Marchiano, Emily; Spinazzi, Eleonora F.; Strojan, Primož; Baredes, Soly; Eloy, Jean Anderson
Abstract : Objective: Laryngeal verrucous carcinoma (LVC) is a rare, locally invasive neoplasm comprising 1% to 3.4% of laryngeal carcinomas. Management strategies are a topic of ongoing conversation, and no definitive treatment protocol based on T stage and presentation exists. This review examines characteristics, treatment modalities, and patient outcomes of LVC. Data Sources: PubMed, MEDLINE, EMBASE, and Web of Science. Methods: Databases were searched through October 29, 2015, for literature detailing individual patient cases of LVC. Variables analyzed included patient demographics, tumor characteristics, tumor size, treatment, and outcomes. Results: Thirty‐seven articles with 369 cases were included. LVC was found more commonly in males (13.8:1), at an average age of 58.7 years, and located in the glottis (74.0%). Most patients had local disease at presentation (94.9%). The most common presenting symptom was hoarseness (92.3%). The most common primary treatment was surgery alone (72.3%), with local excision as the most common technique (56.8%). In patients with data available on both surgical modality and T stage, most patients who presented as T1 and were managed surgically underwent local excision (79.2%). Surgical treatment alone led to high rates of disease‐free survival at follow‐up (86.8%). A large number of patients presenting with T1 disease were disease free at follow‐up (88.6%). Overall survival was 80.3%. Conclusion: LVC is most often managed surgically. The extent of surgical resection may be guided by T stage, with smaller tumors resected via local excision and larger tumors via partial or total laryngectomy. Regardless of T stage or therapy, LVC has a good posttreatment prognosis.